PLACE AND FEATURES OF THE MEDICAL TOURISM IN THE TOURISM SYSTEM (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
Nowadays the medical tourism is organized in different geographical environments and its study is very important. In the article a thorough analysis is performed connected with the medical tourism arrangement features in different regions of the world, standards are determined․
Keywords: medical tourism; active tourism; passive medical tourism; medicinal bathing; medical mud